Relating Dike Geometry and Injection Rate in Analogue Flux-Driven Experiments - Galetto, Federico; Bonaccorso, Alessandro; Acocella, Valerio (Frontiers in Earth Science, 2021)
Dikes feed most eruptions, so understanding their mechanism of propagation is fundamental for volcanic hazard assessment. The variation in geometry of a propagating dike as a function of the injection rate remains poorly studied. Here we use experiments injecting water into gelatin to investigate the variation of the thickness, width and length of a flux-driven dike connected to its source as a function of the injection time and intruded volume. Results show that the thickness of vertically propagating dikes is proportional to the injection rate and remains constant as long as the latter is constant. Neither buoyancy nor injected volume influence the thickness. The along-strike width of the dike is, however, proportional to the injected volume. These results, consistent with the inferred behavior of several dikes observed during emplacement, open new opportunities to better understand how dikes propagate and also to forecast how emplacing dikes may propagate once their geometric features are detected in real-time through monitoring data.